Anglerfish discard estimates and patterns in Spanish Northeast Atlantic trawl fisheries - Díaz-Conde, María Paz; Santos-Blanco, Juan; Velasco, Francisco; Serrano, Alberto; Pérez-Contreras, María Nélida (ICES Journal of Marine Science, 2008)
Estimates of Spanish bottom trawl discards of anglerfish Lophius budegassa and Lophius piscatorius in the Northeast Atlantic Ocean are presented. Both species are commercially valuable in ICES Subareas VI and VII, and Divisions VIIIc and IXa. Information was obtained from observers on board during discard-monitoring programmes. Raising by effort, rather than by landings and target species, was used to determine the total annual discards by weight and number, the discard percentage, and the discard length distribution by stock throughout the dataseries. By weight and number, discards varied interannually, ranging from 4 to 600 t (∼28 000–7 000 000 fish) in northern stocks of anglerfish, and from 1 to 100 t (∼20 000–400 000 fish) in southern stocks. The discard percentage for both species and northern and southern stocks therefore ranged between 2 and 76% by number. Length distributions of the discarded anglerfish show that most were juveniles, although the pattern differed in years with high or with low rates of discarding. The number of juveniles caught apparently increased in most areas after 2000. Correlations between the quantities discarded and recruitment indices from French and Irish trawl surveys were found for northern stocks and with Spanish trawl survey indices for southern stocks. Sí